Edusoft program and teacher performance in secondary public schools - Esteban Huamani, Teodoro (2019)
The NTIC are used in an inadequate way and are caused by the limited knowledge, understanding and application of the NTICS by teachers and if this situation is reversed as we found in this study can benefit: improving teaching performance and learning ability of students, we found that the use of these tools in teaching can motivate the improvement of teaching performance and student learning and that after class hours they will use the NTIC properly for the benefit of a better future.